Teologi Lingkungan dalam Al-Qur’an Perspektif Ibrahim Abdul Matin - Muhammad Amiruddin; Masiyan M. Syam; Jamaluddin Arsyad (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine environmental issues and their resolution through the lens of Islamic environmental theology, drawing on Ibrahim Abdul Matin’s ideas. The focus is to explore how Islamic teachings from the Qur'an and Hadith can provide a theological foundation for addressing environmental challenges and raising Muslim awareness of the environmental crisis. Using a qualitative library research method, data from relevant primary and secondary sources are collected and analyzed based on predetermined categories. The findings reveal that Islam's environmental theology rests on six key principles: Tauhid (God’s unity with creation), Reflecting on God’s Signs, Khalifah (Earth stewardship), Amanah (Trust), ‘Adl (Justice), and Mizan (Balance). These principles affirm that environmental preservation is a spiritual obligation in Islam and promote human responsibility toward nature.